Early Detection Program for Breast and Cervical Cancer in Indonesia: How is Implementation? - Azriful Azriful; Syamsul Alam; Mufti As Siddiq (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2022)
Breast and cervical cancer have ranked first and second in terms of the highest cancer cases in Indonesia. The high incidence of breast and cervical cancer is due to the low coverage of early detection. This study aimed to examine the implementation of breast cancer early detection programs using the SADANIS method and cervical cancer using the IVA method. This current study used a qualitative and descriptive approach through input, process, output, and impact variables. Data was collected through in-depth interviews, observation, and documentation review. The results revealed that the number of trained human resources, facilities, and infrastructure was sufficient. The program had also implemented online and offline information systems and was actively conducting inspections integrated with the “Family Planning” program. The high achievement of the program had also been supported by the existence of an innovative screening system and direct examination in the community. The program achievements for 2021-2022 (January-June) and cases of cervical cancer had decreased. Implementing the early detection program for breast and cervical cancer is considered better. It can thus become a model for other regencies.